2017
DOI: 10.5505/tjtes.2017.37906
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Pediatric Traumatic Brain Injury: Implementations from a Tertiary Pediatric Intensive Care Facility

Abstract: Mortality rate was 12.5%; six patients progressed to brain death with organ donor approvals in five. Initial hypotension, lung contusion, injury severity scores and Rotterdam-CT scores were related with mortality. Rotterdam-CT score was determined as the independent risk factor for mortality; one increment in the score increased the odd of recovery by 20.334 times (%95 CI 1.999-206.879). ISS score was also borderline significant (p=0.052; OR:1.195 %95 CI 0.999-1.430).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…We found the mean Rotterdam scale score of our patients as 2.03, where this score showed significant differences among mild, moderate, and severe traumatic brain injuries. Similarly, Atike Ongun et al [4] found that the mean Rotterdam scores were increasing as the severity of head trauma increased. They reported Rotterdam scores of 1.74 ± 0.77, 2.0 ± 0.53, and 3.83 ± 1.48, for mild, moderate, and severe traumatic brain injury groups, respectively [4].…”
Section: Discussion/conclusionmentioning
confidence: 91%
See 2 more Smart Citations
“…We found the mean Rotterdam scale score of our patients as 2.03, where this score showed significant differences among mild, moderate, and severe traumatic brain injuries. Similarly, Atike Ongun et al [4] found that the mean Rotterdam scores were increasing as the severity of head trauma increased. They reported Rotterdam scores of 1.74 ± 0.77, 2.0 ± 0.53, and 3.83 ± 1.48, for mild, moderate, and severe traumatic brain injury groups, respectively [4].…”
Section: Discussion/conclusionmentioning
confidence: 91%
“…Similarly, Atike Ongun et al [4] found that the mean Rotterdam scores were increasing as the severity of head trauma increased. They reported Rotterdam scores of 1.74 ± 0.77, 2.0 ± 0.53, and 3.83 ± 1.48, for mild, moderate, and severe traumatic brain injury groups, respectively [4]. We have found that patients with severe traumatic brain injury were more likely to be multi-trauma patients.…”
Section: Discussion/conclusionmentioning
confidence: 91%
See 1 more Smart Citation
“…Today, in continuous monitoring of ICP in patients admitted to neuro-intensive care unit, ICP is often measured using a parenchymal sensor. In infants, there are two additional possibilities to indirectly evaluate ICP; (1) by palpating the open anterior fontanelle and cranial sutures, and (2) by serial measurements of head circumference. Although palpation of the anterior fontanelle can be used for screening of patients for further investigations, neither palpation nor head circumference are used in management of acute severe pediatric TBI (15).…”
Section: Icp Monitoring Technologymentioning
confidence: 99%
“…Traumatic brain injury (TBI) is one of the leading causes of mortality among children and adolescents, and a great contributor to morbidity (1,2). The annual incidence of reported TBI cases per 100.000 people (due to all causes) is higher in high-income countries than in low-and middle-income countries (3), with an annual incidence of children with a TBI related emergency department visit estimated to 691 per 100.000, hospitalization due to TBI to 74 per 100.000 and TBI related death to 9 per 100.000 (4).…”
Section: Introductionmentioning
confidence: 99%